The Effect of Gender and Origin on The Speech Accommodation of Irbidians - Marashdeh, Mohammed Mahmoud; Lah, Salasiah Che; Wang, Jianning; Rahman, Muhammad Mushfiqur (European Publisher, 2019)
This study aims at investigating speech style adjustments among Jordanians living in Irbid as well as the reason for the adaptation along with the frequency and consequences. The two variables: /q/, /ϴ/ are the study's concern because of their sensitivity to sound variation. Most studies about language variation among Arabic speakers focus only on social parameters ignoring the interlocutors' psychology causing affecting such variation. accordingly, this study employs the Communication Accommodation Theory (CAT) framework to grasp also the interlocutor’s psychological manner. This theory posits the influence of the addresser on the addressee, and vice versa in the speech style adjustment. Additionally, accommodation happens gain the interlocutor’s likeness if there is no identity threat. Meanwhile, asserting identity and distinction invokes language divergence. The respondents were 12 selected randomly and divided in terms of sex and origin. The findings reveal women of both origins are more apt to use a prestigious linguistic form of /q/ and /ϴ/. Men of both origins prefer to use more of the standard form of /ϴ/. However, those of Palestinian origin are keener to adapt their /q/ variant to the host's one. Hence, women and men have different linguistic behaviors. Women are more prestigious in their speech regardless of origin, while men of immigrants' origin find it better to drop the marked items to be more acceptable to the host's community.